Associations Between Human Milk Oligosaccharides at 1 Month and Infant Development Throughout the First Year of Life in a Brazilian Cohort. Issue 11 (7th September 2021) - Ferreira, Ana Lorena L; Alves-Santos, Nadya H; Freitas-Costa, Nathalia C; Santos, Pedro P T; Batalha, Mônica A; Figueiredo, Amanda C C; Yonemitsu, Chloe; Manivong, Nadia; Furst, Annalee; Bode, Lars; Kac, Gilberto
ABSTRACT: Background: Human milk oligosaccharides (HMOs) are unconjugated glycans associated with infant health and development. Objectives: To investigate the associations between HMO concentrations at 1 month and infant development throughout the first year of life. Methods: A prospective cohort of Brazilian women between 18–40 years of age and their infants was studied from baseline (between 28–35 gestational weeks) and followed at 1 ( n = 73), 6 ( n = 51), and 12 months ( n = 45). A total of 19 HMOs were quantified by HPLC with fluorescence detection. Infant development was evaluated by the Brazilian Ages and Stages Questionnaire. A directed acyclic graph was used to define the minimally sufficient adjustment (gestational age at birth, gestational weight gain, prepregnancy BMI, maternal age, parity, and the mode of breastfeeding at 1 month). Cox regression models with HRs and Benjamini-Hochberg multiple corrections were performed to estimate associations of HMOs with the cumulative risk of inadequate development for 5 developmental domains or for ≥2 developmental domains in all women and in the subset of secretor women (defined as the presence or near absence of 2′-fucosyllactose and lacto-N-fucopentaose I). Results: The multivariate models with multiple corrections revealed an inverse association between lacto-N-tetrose (LNT) and the risk of inadequate development for personal-social skills (0.06; 95% CI: 0.01–0.76) and for ≥2 developmental domains (0.06; 95% CI: 0.01–0.59). The secretor mothers analysis also showed inverse associations with slightly different results for personal-social skills (0.09; 95% CI: 0.02–0.84) and ≥2 developmental domains (0.05; 95% CI: 0.01–0.70). Conclusions: Higher concentrations of LNT HMOs in Brazilian women are associated with their infants being less likely to be at risk of inadequate development for personal-social skills or for ≥2 developmental domains during the first year of life.